Nanomagnetic Gears With Electrically Controlled Transmission Ratio - Maddalena Fiorentino; Davi Rodrigues; Riccardo Tomasello; Mario Carpentieri; Giovanni Finocchio; Francesca Garesci (IEEE Open Journal of Nanotechnology)
Magnetic gears offer a reliable and vibration-free alternative to traditional mechanical gears. At the micro- and nanoscale, electrical manipulation of magnetic domains can further enhance the performance and versatility of these gears. In this work, we introduce the concept of electrically tunable magnetic nanogears and propose a nanomagnetic gear design that operates at the mesoscopic scale and exploits the electrical manipulation of magnetic textures and stray field coupling to achieve precise, contactless and tunable torque transmission. This device concept is scalable and offers a continuously adjustable electrical transmission ratio between two gears by exploiting the spin-orbit torque observed in nanomagnetic devices. We have analyzed the coupling of magnetic domains in two parallel circular nanotracks, each serving as a rotor in the gear system, using experimentally realistic material parameters. By exploiting the current-driven motion of the magnetic domains, we derive an ideal transmission ratio given by ω2/ω1 = 1 + ωd/ω1 where ω2 and ω1 are the mechanical angular velocities of the driven (output) and driving (input) rotors, respectively, and ωd(J) is the current-driven angular velocity of the magnetic domains valid when the two rotors are fully coupled via stray fields. Numerical calculations show that this nanogear can work up to current densities J of 4.1012 A/m2 and distances of 30 nm. This work paves the way for the development of a new generation of highly tunable nanomagnetic gears with potential applications in nano-actuators, micromachines and other nanoscale devices.